VD_FINDINFO HC / 2014 / 768 vom 25. September 2014 - VD Tribunal cantonal (2014)
DROIT DE GARDE, GARDE ALTERNÉE, PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 176 CC